A Flexible Impact of Affective Feelings on Priming Effects: Assimilation and Contrast. (April 2014) - Huntsinger, Jeffrey R.
Four experiments found that positive and negative affect dictated whether primed social categories and trait concepts led to assimilation or contrast. This influence was further found to be flexibly responsive to the momentary activation of a global or local focus. When a global focus was dominant, positive affect resulted in assimilation to primed traits and social categories, and negative affect resulted in contrast. But, when a local focus was dominant, the opposite pattern of assimilation and contrast as a consequence of positive and negative affect was observed. These results are consistent with the more general view that positive and negative affect signal the value of currently accessible response tendencies and are, therefore, flexibly responsive in their influence cognition to changing situations and mental contexts.